Temporomandibular disorder among metamphetamine user - Happysari, Septyana; Tanti, Ira (Indonesian Journal of Prosthodontic, 2020)
Cystalline metamphetamine or often called "shabu shabu" is a type of amphetamine which is the most often abused in Indonesia. Cinical symptoms of temporomandibular disorder (TMD) were found in 84.2% of 152 among amphe-tamine users. This case analysis aims to evaluate the treatment of TMD of muscular origin, with myofacial pain diagnosis. The chosen treatments are maximizing etiology-related education and supportive care that aims to reduce muscle mastication activities such as physical self-regulation, assisted muscle stretching, warm compresses, and administration of analgesics to reduce pain that patients often experience.